Does local vancomycin powder impregnated with autogenous bone graft and bone substitute decrease the risk of deep surgical site infection in degenerative lumbar spine fusion surgery?—An ambispective study - Po-Hsin Chou; Hsi-Hsien Lin; Yu-Cheng Yao; Ming-Chau Chang; Chien-Lin Liu; Shih-Tien Wang (BMC Musculoskeletal Disorders, 2022)
Abstract Background Deep surgical site infection (DSSI) is one of the most challenging complications in lumbar fusion surgery. Few investigations examined the effect of vancomycin powder mixed with autogenic bone graft (ABG) and bone substitutes on preventing DSSI in degenerative lumbar fusion surgeries as well as any interference with bony fusion. The aim of the study was to investigate the effects of ABG along with bone substitutes as a local vancomycin delivery system on preventing DSSI in lumbar instrumented fusion and compared with those who did not use vancomycin powder. Methods From January, 2015 through December, 2015, a one-year prospective study using vancomycin powder mixed with ABG and bone substitute for degenerative lumbar fusion surgeries as vancomycin (V) group, 1 gm vancomycin for 2 and 3-level, and 2 gm for more than 3-level instrumentation. From December, 2013 through December 2014, patients received degenerative lumbar fusion surgeries without using vancomycin before the vancomycin protocol were retrospectively enrolled as non-vancomycin (NV) group. Vancomycin concentration was checked at post-operative days 1 and 3 for both the serum and drainage. Patients’ demographic data, microbiology reports, fusion status and functional outcomes were evaluated. Results One hundred and ten patients were enrolled prospectively in the V group, and 86 for the NV group. After an average 41 months follow-up (range, 36–54), 3 patients (3.48%) developed postoperative DSSIs in the NV group, thereby requiring revision surgeries and parenteral antibiotics treatment versus no DSSIs (0%, 0/100) in the V group. (p = 0.048). The postoperative serum vancomycin levels were undetectable and no vancomycin related side effects was encountered. The mean vancomycin concentration of drainage at postoperative days 1 and 3 were 517.96 ± 174.4 and 220.14 ± 102.3 μg/mL, respectively. At final follow-up, there was no statistical difference observed in terms of clinical and radiologic outcomes. Conclusions Our vancomycin protocol may reduce the incidence of DSSI in degenerative lumbar fusion surgery without affecting bony fusion. Level of Evidence Level III ambispective comparative study.